A Comparative Analysis of Epoxy Coating Quality on ASTM AH-36 Steel Plates Using Surface Preparation Methods - Rahmat Hidayat; Rando Tungga Dewa; Thaha Yassin Ramadhan Utomo; Muhammad Rizky; Mariyan Maritza Ramadhan; Leander Berliano Farel Kristiyono; Ainur Rofiq (Jurnal Rekayasa Mesin, 2026)
The shipping industry, vital to the global economy, faces significant challenges due to corrosion in marine environments, particularly affecting steel structures like AH36 grade used in ships. This study investigates the effectiveness of two surface preparation methods—Abrasive Blast Cleaning and Power Tool Cleaning—on the adhesion of epoxy coatings, which are essential for enhancing corrosion resistance. Employing ASTM standards, we assessed surface roughness and adhesion strength, revealing that Abrasive Blast Cleaning produced a superior average roughness of 106.34 µm compared to 17.67 µm from Power Tool Cleaning. The Tape X-Cut test further demonstrated that the former achieved a perfect adhesion rating of 5A, while the latter only reached 4A, indicating slight peeling. These findings underscore the critical role of surface preparation in optimizing coating performance, suggesting that adopting Abrasive Blast Cleaning can significantly extend the lifespan and operational efficiency of both commercial and military vessels. This research not only addresses the urgent need for improved protective measures in the shipping sector but also contributes to reducing economic losses attributed to corrosion, estimated at 3-4% of GDP annually.